Commodity reference price transparency: conceptualization, measurement instrument development, and influence on commodity price management. - Vašek, Jan (Cranfield University, 2023)
Commodity reference price (CRP) is potentially an important commodity price management influencing factor. However, despite its importance, it remains under-researched and poorly understood. Anchored in contingency theory and building on previous studies, this study (a) conceptualizes CRP contingency as CRP transparency, (b) creates a CRP transparency index as a tool for classifying and evaluating CRP, and (c) demonstrates the CRP transparency impact on CRP functions and CPM practices. Intuitive and interpretive literature reviews are combined with nine directed expert interviews to uncover the CRP transparency attributes. Subsequently, 111 interviews with purchasing managers explore a purposive sample of 22 CRP to construct and populate the CRP transparency index and to explore its theoretical and practical relevance, in particular, how individual CRP transparency levels shape CRP functions and impact the availability, choice and performance of commodity price management practices. The main contributions of this thesis to theory are (a) conceptualizing CRP transparency as a multi-dimensional construct composed of four measured attributes: accuracy, completeness, publication frequency, and methodology, (b) operationalizing these measured attributes into five transparency levels, (c) constructing CRP transparency index divided into five distinct and meaningful levels following a geological metaphor: black hole, opaque, translucent, transparent, dazzle. From a practitioner standpoint, this thesis provides actionable insights into (i) CRP transparency assessment and comparison with alternative CRP, (ii) how CRP transparency shapes the commodity price management practices and CRP functions and, (iii) offers an empirical toolbox for assessing, comparing, and configuring CRP to regulators and CRP issuers.
Keywords: Commodity reference price; Commodity price management; Commodities; Contingency theory; Composite index; Commodity reference price practices